2021
DOI: 10.1002/pc.26420
|View full text |Cite
|
Sign up to set email alerts
|

A review on high thermally conductive polymeric composites

Abstract: Polymers are known as thermally insulated materials with reported effective thermal conductivity (K eff ) in the range of 0.1 to 0.5 Wm À1 K À1 . However, increasing demand for smaller and more powerful electronics has created the need for thermally conductive polymers for use in heat exchangers and electronic packaging applications. Given this background, much research has been done over the past two decades to increase the K eff of polymers. Based on the strategy involved, those works can be divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 237 publications
(172 reference statements)
0
27
0
Order By: Relevance
“…Sufficient hydrogen bonds in the interpenetrating networks can provide pathways for electrons transportation to the SMPI-PANI composites. [35][36][37]…”
Section: Electrical Resistivitymentioning
confidence: 99%
“…Sufficient hydrogen bonds in the interpenetrating networks can provide pathways for electrons transportation to the SMPI-PANI composites. [35][36][37]…”
Section: Electrical Resistivitymentioning
confidence: 99%
“…[ 57 ] The incorporation of BN and CNC hybrid filler into biodegradable composites expands its applicability in fields also including mechatronics, [ 58 ] implants, [ 59 ] hydrogel, [ 24 ] thermal management, [ 60 ] biomedical, [ 61 ] and thermal conductive applications. [ 62 ]…”
Section: Introductionmentioning
confidence: 99%
“…[57] The incorporation of BN and CNC hybrid filler into biodegradable composites expands its applicability in fields also including mechatronics, [58] implants, [59] hydrogel, [24] thermal management, [60] biomedical, [61] and thermal conductive applications. [62] This study aims to fabricate the hybrid hydroxylated BN/PVA film via a solution casting method impregnated with CNC. The influence of hybrid hydroxylated BN and CNC on the physical, thermal, and mechanical properties of the resultant BN/CNC/PVA film was studied.…”
mentioning
confidence: 99%
“…Early work in the field of polymer composites for controlling the distribution of fillers often employed several methods to create homogeneous dispersion of fillers in the matrix, such as sonication, [55,56] mixing, [57][58][59] and high shearing. [60,61] Building on these efforts, it was found that controlling filler distribution is advantageous for enhancing composite properties in many practical applications, [62][63][64][65][66] particularly through developing interconnected (networklike) or macroscopically oriented filler morphology. For example, aligning reinforcing agents in the polymer matrix along the thickness direction can improve the ability of composites to withstand external force, [63,67,68] through effective dissipation of locally concentrated energy.…”
Section: Introductionmentioning
confidence: 99%